Foreign bank entry, deregulation and bank efficiency: Lessons from the Australian experience - Sturm, Jan-Egbert; Williams, Barry (Journal of Banking & Finance, 2004)
This study considers the impact of foreign bank entry on banking efficiency in Australia during the post-deregulation period 1988–2001. Using Data Envelopment Analysis, Malmquist Indices and stochastic frontier analysis, we find foreign banks more efficient than domestic banks, which however did not result in superior profits. Major Australian banks have used size as a barrier to entry to new entrants. Furthermore, bank efficiency has increased post-deregulation and the competition resulting from diversity in bank types was important to prompt efficiency improvements. Finally, the recession of the early 1990s resulted in a distinct shift in the process of efficiency changes.